The prevalence of obstructive sleep apnea in patients hospitalized for COPD exacerbation - Turčáni, Pavel; Skřičková, Jana; Pavlík, Tomáš; Koriťáková, Eva; Orban, Marek (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2015)
BACKGROUND: The concurrence of obstructive sleep apnea (OSA) and chronic obstructive pulmonary disease (COPD) is generally identified as an overlap syndrome. Only limited evidence is available on the prevalence of OSA in patients with stable COPD, and essentially no data on the prevalence of OSA in patients hospitalized for COPD exacerbation. The aims of the study were to determine the ratio of concurrence of OSA in patients hospitalized for COPD exacerbation and to identify the confounders of OSA detected in COPD subjects. METHODS: 101 patients were hospitalized for COPD exacerbation at the Department of Respiratory Diseases in the course of four months. Seventy-nine consecutive patients were enrolled in the study and in 35 of these subjects polygraphy was performed. Descriptive statistics, Mann-Whitney test, Kruskal-Wallis test, Spearman correlation and Fisher's test were used to summarize and evaluate results. RESULTS: In 18 (51.4%) subjects with polygraphy examination, the apnea-hypopnea index (AHI) ≥ 5 indicated the presence of OSA. The AHI value, and thus the severity of the sleep disorder, correlated with the class of the Mallampati score, presence of snoring, apnea, coronary heart disease, diabetes mellitus in patient's history, height, body mass index, neck, waist and hip circumferences, and the value of the Epworth sleepiness scale. CONCLUSION: Polygraphy performed in patients hospitalized for exacerbation of COPD indicated an increased prevalence of OSA compared to the general population and stable COPD patients.
Keywords: rizikové faktory; senioři; následné studie; Pulmonary Disease, Chronic Obstructive; chronická obstrukční plicní nemoc; Follow-Up Studies; Disease Progression; Female; Male; Aged; Middle Aged; Česká republika; pletysmografie; Oxygen Consumption; Prospective Studies; Sleep Apnea, Obstructive; Plethysmography; mužské pohlaví; spotřeba kyslíku; index tělesné hmotnosti; ženské pohlaví; obstrukční spánková apnoe; Adult; Risk Factors; Czech Republic; Body Mass Index; stupeň závažnosti nemoci; senioři nad 80 let; dospělí; lidé středního věku; prospektivní studie; Aged, 80 and over; Prevalence; lidé; Humans; Severity of Illness Index; prevalence; progrese nemoci